(untitled) (Journal of Economics, Law and Society, 2025)
Investments and allocations in research and development (R&D) represent a main driver of competitive advantage, innovation, and sustainable growth for the most reputable IT companies in Bosnia and Herzegovina. This study empirically examines the impact of R&D expenditures on corporate performance and market value over the period 2022–2024, using comprehensive and balanced data that ensures high analytical precision. Descriptive statistics indicate significant variability in the expected growth rate measured by the DCF method, while correlation analysis confirms positive and statistically significant relationships between R&D expenditures and key performance indicators (ROA, ROE, DCF), with stronger links observed in 2023 and 2024. Regression analyses, including models with lagged effects from previous periods, demonstrate that increased R&D allocations significantly enhance current and future profitability, market value growth, and competitive positioning, with variations depending on year and indicator. The results underscore the strategic importance of continuous and well-planned R&D investments for achieving sustainable growth, creating comparative advantages, and maximizing corporate value, providing empirical evidence and practical implications for managers and investors in the IT sector in Bosnia and Herzegovina.